Performance analysis of spectrum sensing methods: a numerical approach - Hasan, Mohammad Kamrul; Ismail, Ahmad Fadzil; Hassan Abdalla Hashim, Aisha; Mohd. Ramli, Huda Adibah; Islam, Shayla; Hashim, Wahidah (IEEE, 2014)
Recent enhancement of Long Term Evolution / Advanced (LTE/LTE-A) is aimed to increase the throughput of the Orthogonal Frequency Division Multiplexing (OFDM) system. This is quite obvious where both frequency and time division are employed in order to augment the system capacity. In LTE/LTE-A heterogeneous Networks (HetNets), femtocells (HeNodeBs) are the optimal choice to extend the coverage within indoor environment. Nonetheless, the deployment of such base stations, somewhat to certain extent, does create cross-tier and co-tier interferences with the macrocell users (UEmacro-eNB) that ostensibly can become a critical challenge. It is implied that the unutilized / idle spectrums reallocation might be one of the solutions to mitigate such challenge. However, the errorless spectrum sensing does pose another issue. This paper outlines the investigation findings where spectrum sensing techniques is deployed to maximize the spectrum detection capacity with minimum error in OFDM based HetNets. In addition, in the attempt to increase the efficiency of spectrum resources, this paper proposes a sensing technique which is imposed over advanced energy detection technique to detect the idle spectrums. The result of the proposed scheme is evaluated using Monte Carlo simulation.